Loss of prolyl hydroxylase-1 protects against colitis through reduced epithelial cell apoptosis and increased barrier function - Tambuwala, Murtaza M.; Cummins, Eoin P.; Lenihan, Colin R.; Kiss, Judit; Stauch, Markus; Scholz, Carsten C.; Fraisl, Peter; Lasitschka, Felix; Mollenhauer, Martin; Saunders, Sean P.; Maxwell, Patrick H.; Carmeliet, Peter; et al. (Gastroenterology, 2010)
Background & Aims - Hypoxia inducible factor (HIF) prolyl hydroxylase inhibitors are protective in mouse models of inflammatory bowel disease (IBD). Here, we investigated the therapeutic target(s) and mechanism(s) involved. - Methods - The effect of genetic deletion of individual HIF-prolyl hydroxylase (PHD) enzymes on the development of dextran sulphate sodium (DSS)-induced colitis was examined in mice. - Results - PHD1−/−, but not PHD2+/− or PHD3−/−, mice were less susceptible to the development of colitis than wild-type controls as determined by weight loss, disease activity, colon histology, neutrophil infiltration, and cytokine expression. Reduced susceptibility of PHD1−/− mice to colitis was associated with increased density of colonic epithelial cells relative to wild-type controls, which was because of decreased levels of apoptosis that resulted in enhanced epithelial barrier function. Furthermore, with the use of cultured epithelial cells it was confirmed that hydroxylase inhibition reversed DSS-induced apoptosis and barrier dysfunction. Finally, PHD1 levels were increased with disease severity in intestinal tissue from patients with IBD and in colonic tissues from DSS-treated mice. - Conclusions - These results imply a role for PHD1 as a positive regulator of intestinal epithelial cell apoptosis in the inflamed colon. Genetic loss of PHD1 is protective against colitis through decreased epithelial cell apoptosis and consequent enhancement of intestinal epithelial barrier function. Thus, targeted PHD1 inhibition may represent a new therapeutic approach in IBD.